Empirical Analysis of Demand for Imports in Sub-Saharan Africa. Issue 4 (4th July 2021) - Asaana, Clement Agonyim; Sakyi, Daniel
ABSTRACT: This article investigates the drivers of demand for imports of goods and services in a panel of 32 sub-Saharan African countries over the 1990 to 2016 period with the aid of an imperfect substitute model of import demand and the dynamic system-GMM technique. For comparison purposes, three separate models are estimated: imports of goods and services, imports of goods, and imports of services. The article finds that expenditure components, relative import prices, and foreign exchange reserves are the key drivers of import demand in sub-Saharan Africa. The findings and policy suggestions of the study provide relevant information for policy formulation.